Korean law in the Global Economy - Nottage, L (Victoria University of Wellington Law Review, 1996)
This article is a book review of Sang-Hyun Song (ed) Korean Law in the Global Economy (Bak Young Sa Publishing Co, Seoul, 1996) 1500 + viii pages (including index), US$197 (including airmail, tax and handling). The book is a key reference text that covers virtually all aspects of Korean law relevant to New Zealanders, with the author arguing that it belongs in every New Zealand library. While the book suffers from the occasional typographical error, Nottage concludes that the book is an excellent resource, and Professor Song has succeeded in his aim of offering the means to achieve a basic understanding of the Korean law and legal system as they operate in the real world.